Ectopic ovarian pregnancy following in vitro fertilization: case report - Khandelwal, Shrinkhla; Natu, Neeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian pregnancy is a rare form of extrauterine ectopic pregnancy. Risk factors such as reproductive treatments and infertility have been identified in recent studies. In this article, we present a case of ovarian ectopic pregnancy occurring following in vitro fertilization treatment and a fresh embryo transfer. The diagnosis of ovarian pregnancy was made during transvaginal sonography performed due to suspected ectopic pregnancy. Ovarian ectopic pregnancy is a rare clinical phenomenon. Late diagnosis and lack of appropriate intervention may have catastrophic results. Several mechanisms and risk factors are proposed, and their acknowledgment may improve early diagnosis and prevention of complications.